2011
DOI: 10.1093/nar/gkr484
|View full text |Cite
|
Sign up to set email alerts
|

Unique translation initiation of mRNAs-containing TISU element

Abstract: Translation Initiator of Short 5′ UTR (TISU) is a unique regulatory element of both transcription and translation initiation. It is present in a sizable number of genes with basic cellular functions and a very short untranslated region (5′ UTR). Here, we investigated translation initiation from short 5′ UTR mRNAs with AUG in various contexts. Reducing 5′ UTR length to the minimal functional size increases leaky scanning from weak and strong initiators but hardly affects translation initiation and ribosomal bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 31 publications
10
113
0
Order By: Relevance
“…Silvestrol inhibited cap‐dependent translation of Renilla luciferase, but the translation driven by the TISU sequence was only marginally inhibited (Fig 4A) as expected (Elfakess et al , 2011). In contrast, silvestrol stimulated HCV IRES‐driven translation of an F‐Luc reporter, which was included as a transfection control (Fig EV3H).…”
Section: Resultssupporting
confidence: 84%
“…Silvestrol inhibited cap‐dependent translation of Renilla luciferase, but the translation driven by the TISU sequence was only marginally inhibited (Fig 4A) as expected (Elfakess et al , 2011). In contrast, silvestrol stimulated HCV IRES‐driven translation of an F‐Luc reporter, which was included as a transfection control (Fig EV3H).…”
Section: Resultssupporting
confidence: 84%
“…mRNAs with short 5 ′ UTRs, encoding proteins with mitochondrial function, were enriched (4.7-fold enrichment, P = 0.03) for translation initiator of short 5 ′ UTR (TISU) elements ( Fig. 3D,E; Elfakess et al 2011). Thus, in addition to TOP mRNAs, MTOR-sensitive mRNAs include non-TOP mRNAs with long 5 ′ UTRs, which encode proliferation-and survival-promoting proteins, and a subset of mRNAs with short (<30 nt) 5 ′ UTRs that were enriched with TISU elements (Fig.…”
Section: Low Sensitivity Limits the Catalog Of Mtor-sensitive Mrnas Imentioning
confidence: 99%
“…Expression of proteins encoded by a subset of MTOR-sensitive mRNAs harboring short 5 ′ UTRs requires EIF4E but is largely unaffected by EIF4A1 TISU elements render mRNA translation sensitive to MTOR but not to EIF4A inhibition (Elfakess et al 2011). We therefore depleted EIF4E or EIF4A1 in MCF7 and HEK293E cells and monitored expression of proteins encoded by MTOR-sensitive mRNAs with either long (CCND3, MCL1, BIRC5, and BCL2) or short (ATP5O, ATP5G1, NDUFS6, and UQCC2) 5 ′ UTRs.…”
Section: Low Sensitivity Limits the Catalog Of Mtor-sensitive Mrnas Imentioning
confidence: 99%
“…mechanism under an inhibited translation state, as induced by nutrient starvation (28)(29)(30). However, target of rapamycin complex 1 (TORC1) has been shown to be the main regulator of TOP mRNA translation through the phosphorylation of 4E-BP and S6K proteins under nutrient availability conditions (31).…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…One interesting finding consisted of the rhythmic regulation of TISU genes (28,29). Recently, it was shown that these genes are protected from AMPK-induced translation inhibition (30), and the rhythmic activation of the AMPK pathway thus provides an explanation for their rhythmic translation activation (12,60).…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%